Intergenerational Marijuana Use: A Life Course Examination of the Relationship between Parental Trajectories of Marijuana Use and the Onset of Marijuana Use by Offspring - Augustyn, Megan Bears (Psychol Addict Behav, 2019)
Prior research documents intergenerational (IG) continuity in marijuana use, with most work adopting a life course perspective. Incorporating a methodology that allows for the measurement of “patterns of behavior” instead of singular aspects of parent marijuana use (e.g., age of onset or frequency at any one age or ages), we investigated the simultaneous effects of parental age of onset, frequency, and duration of marijuana use across three periods of the life course (i.e., adolescence, emerging adulthood, and adulthood) on the timing of first marijuana use among offspring. Using prospective data from two companion studies, the Rochester Youth Development Study and the Rochester Intergenerational Study, we used group-based trajectory models to estimate trajectories (or patterns) of parental marijuana use spanning ages 14 to 31 among a birth cohort of 462 parents. We then examined the relationship between parental trajectories of marijuana use and the timing of the onset of marijuana use through age 25 among firstborn offspring. Both late-onset persistent use by parents and increasing chronic use spanning adolescence to adulthood by parents were associated with an increased likelihood of onset of marijuana use among offspring. The results underscore the importance of patterns of marijuana use for IG continuity in contrast to singular measures (e.g., age of onset among parents), which can obfuscate important IG patterns of continuity. Prevention and intervention programs should consider the entire history of parent use in order to better identify children most at risk for the onset of marijuana use in adolescence and emerging adulthood.